Hyperpolarized Renal Magnetic Resonance Imaging: Potential and Pitfalls - Laustsen, Christoffer (Frontiers in Physiology, 2016)
The introduction of dissolution dynamic nuclear polarization (d-DNP) technology has enabled a new paradigm for renal imaging investigations. It allows standard magnetic resonance imaging complementary renal metabolic and functional fingerprints within seconds without the use of ionizing radiation. Increasing evidence supports its utility in preclinical research in which the real-time interrogation of metabolic turnover can aid the physiological and pathophysiological metabolic and functional effects in ex vivo and in vivo models. The method has already been translated to humans, although the clinical value of this technology is unknown. In this paper, I review the potential benefits and pitfalls associated with dissolution dynamic nuclear polarization in preclinical research and its translation to renal patients.